A molecular-assisted taxonomic assessment of elasmobranch fishes (Chondrichthyes: Elasmobranchii) from south-eastern Arabia revisited - Henderson, Aaron C.; Reeve, Alan J.; Jabado, Rima W.; Naylor, Gavin J. P. (Zootaxa, 2025)
The first molecular-assisted assessment of shark and batoid taxonomy in the waters of south-eastern Arabia was undertaken almost a decade ago, at a time when many species lineages lacked clear resolution. Consequently, only tentative identifications could be offered in some cases. There has been a considerable amount of focus on elasmobranch taxonomy since then, and this has resulted in numerous revisions to species identities and distributions. Therefore, in light of these more recent findings, mitochondrial NADH2 sequences from the original south-eastern Arabia study were re-assessed and taxonomically updated. This resulted in the recovery of 28 distinct shark lineages, of which all but one could be attributed to currently-recognised species. The remaining lineage most likely represents an undescribed Echinorhinus sp., which has been flagged in previous studies. Twenty-eight batoid lineages were also recovered, 13 of which have undergone taxonomic revision since the original study. Although most of these could be attributed to currently-recognised species, certain lineages remain problematic. Consequently, further work is required to provide a comprehensive assessment of elasmobranch taxonomy in the region.